PENGARUH PROFITABILITAS, LIKUIDITAS DAN LEVERAGE TERHADAP NILAI PERUSAHAAN DENGAN KUALITAS LABA SEBAGAI VARIABEL MODERATING (Studi Kasus Pada Perusahaan Manufaktur Sektor Makanan dan Minuman Yang Terdaftar Di Bursa Efek Indonesia Periode 2019-2021) - Catur Nugroho; Atwal Arifin (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
The purpose of this study was to determine the effect of profitability, liquidity and leverage on firm value with earnings quality as a moderating variable in food and beverage companies listed on the Indonesia Stock Exchange for the 2019-2021 period. The sampling method in this study was purposive sampling, where 42 samples were obtained from companies. Processing the data in this study using the IBM SPSS Statistics version 23 program application. The results of this study indicate that profitability and leverage affect firm value, while firm liquidity has no effect on firm value. Earnings quality does not moderate the relationship between profitability, liquidity and leverage on firm value.